Toward the development of a square wave voltammetry technique for in situ soil organic carbon quantification - Matthew Myers; Praveen; Stuart Watt; Wesley Moss; Joanne Wisdom (Sensing and Bio-Sensing Research, 2025)
Many strategies are being developed and implemented to increase the soil carbon stock; however, demonstrating efficacy is often limited by the time and costs associated with soil sampling/analysis and a lack of real-time data to understand soil carbon spatiotemporal dynamics. As such, the development of real time in-ground sensors for monitoring changes in soil organic carbon over time is necessary to validate (or invalidate) these strategies in the real world. In situ near-IR spectroscopic techniques have been developed for quantifying and characterizing organic carbon in soil. This strategy is strongly affected by soil moisture content, relies on complex statistical and machine learning techniques and is relatively expensive. In this work, we examine the feasibility of developing a low-cost electrochemical technique for the quantification of soluble soil carbon species in soil. Given that these species are very diverse, commercially available fulvic/humic acid is used as a pathway for sensor development. Using a composite film consisting of a poly(methyl methacrylate) resin (to attract fulvic/humic acid to the electrode surface) and a hydrogel material (to bring moisture to the electrode surface), a linear response over a fulvic acid concentration range 0 to 0.05 wt% has been demonstrated. Multi-day measurements in a varying temperature environment have shown that there is a strong correlation between response and temperature. By implementing these correlations and optimizing the coating characteristics, we show that the sensor has a lifetime of over one month in aqueous solution.